Ethnography as tradition in Africa - Pina-Cabral, Joao (2011)
“Ethnography as tradition in Africa” is our way of stressing that our discipline’s favoured methodology is an embodied engagement with the human world with roots in forms of curiosity that are very ancient; they emerged long before academic anthropology was constituted in the mid-nineteenth century. Ethnography, thus, is not open to being reinvented at every new juncture, either as a mode of scientific analysis or as a mode of reporting on experience. In this sense, we too stand in the shoulders of giants. Only seen from the perspective of that historical succession can the contemporary ethnographies we collect in this dossier achieve the full plenitude of their meaning.